Fast and reliable identification of axons, axon initial segments and dendrites with local field potential recording - Petersen, Anders V.; Johansen, Emil Ø.; Perrier, Jean-François (Frontiers in Cellular Neuroscience, 2015)
The axon initial segment (AIS) is an essential neuronal compartment. It is usually where action potentials are initiated. Recent studies demonstrated that the AIS is a plastic structure that can be regulated by neuronal activity and by the activation of metabotropic receptors. Studying the AIS in live tissue can be difficult because its identification is not always reliable. Here we provide a new technique allowing a fast and reliable identification of the AIS in live brain slice preparations. By simultaneous recoding of extracellular local field potentials and whole-cell patch-clamp recording of neurons, we can detect sinks caused by inward currents flowing across the membrane. We determine the location of the AIS by comparing the timing of these events with the action potential. We demonstrate that this method allows the unequivocal identification of the AIS of different types of neurons from the brain.